Dive into English Phonology: Foundational concepts and teaching strategies for novice EFL learners - Deliani, Susy; Yandra, Alexander; Kurniawan, Kurniawan; Yuliana, Angelin (EDUTREND: Journal of Emerging Issues and Trends in Education, 2025)
Mastering English phonology is essential for second language acquisition, as it influences pronunciation accuracy, listening comprehension, and communicative competence. However, beginner English as a Foreign Language (EFL) learners often encounter difficulties due to the complexity of phonological theories and irregular spelling-to-sound correspondences. This study presents a systematic literature review, guided by the PRISMA framework, to examine key challenges and effective teaching strategies in English phonology instruction for beginners. A comprehensive search of Google Scholar and CrossRef databases identified 1,037 records published between 2019 and 2024. After screening and quality appraisal, 25 high-quality studies were included in the synthesis. Findings indicate that articulatory phonology, though theoretically robust, is impractical for classroom application due to its dependence on computational models and language-specific data. Additionally, inconsistencies between English spelling and pronunciation frequently lead to learner errors and reduced confidence. While students improve in recognizing phonetic symbols, current instructional methods often lack interactive, practice-based approaches. The review highlights the need to simplify complex phonological concepts and adopt learner-centered, communicative pedagogies. These insights offer valuable guidance for enhancing phonological competence and communicative effectiveness among novice EFL learners, addressing an important gap in current phonology instruction literature.